Strategi Guru Dalam Meningkatkan Kesadaran Beribadah Siswa - Pela Safni; Murniyetti Murniyetti (An-Nuha, 2022)
This study aims to analyze the strategy of fiqh teachers in increasing students' awareness of worship. This research uses a qualitative method with a case study approach, research data is taken through direct interviews with five informants (deputy head of curriculum, fiqh teacher, and 3 students) who were selected by purposive technique. sampling. To strengthen the interview data, the authors made observations by being directly involved in the learning process in the classroom. All interview and observation data were analyzed thematically using the Miles and Huberman method. Overall, the research findings found three teacher strategies in increasing students' awareness of worship in fiqh subjects. The 3 strategies are: i) doing habituation, ii) setting an example, iii) cooperating with homeroom teachers and parents. The three strategies in this study can be used as reference material for other teachers in increasing students' awareness of worship in fiqh subjects in madrasah.